RANCANGBANGUN PROGRAM KONTROL DATA LOGGER UNTUK PEMANTAUAN KUALITAS AIR MENGGUNAKAN APLIKASI FOSS GNU C++ - Wahjono, Heru Dwi (Jurnal Air Indonesia, 2014)
Online and realtime monitoring system for water quality that uses a computer mainboard as data logger requires software applications that serve to control the sensor work in order to measure the water quality data and sends it to the data center. Some of the requirements such as data measurement, storage and delivery of data and early warning system are required by the data logger in order to have the features as desired by the majority of users of this system. To facilitate the making of the program code, sensor with serial communication ports (RS232C) will be used. Program control data logger that meets these requirements is developed using Water Flow Software Development Life Cycle method and using GNU C++ the free open source software (FOSS) as the development tools. Program control data logger that has been developed will be installed to the data logger hardware and operated using FreeBSD as the Operating system. The program will run on the class 10 of flash drive with 16 giga byte capacity.Ã‚Â Keywords: water quality monitoring, online/realtime monitoring, early warning system (EWS), open source software, data logger, onlimo OSS, control data logger, GNU C++